New heterogeneous catalysts containing platinum group metals recovered from a spent catalytic converter. (25th August 2021) - Racles, Carmen; Zaltariov, Mirela‐Fernanda; Coroaba, Adina; Silion, Mihaela; Diac, Cornelia; Dascalu, Andrei; Iacob, Mihail; Cazacu, Maria
Abstract: A spent catalytic converter was treated with concentrated HCl and hydrogen peroxide in very mild conditions to extract approximately half of its platinum group metals (PGMs) content, mainly as chlorides. The noble metals were subsequently charged into functionalized mesoporous silica by complexation with mercapto groups. A combination of methods was employed to prove the transfer of PGMs and to characterize the materials (inductively coupled plasma optical emission spectrometry [ICP‐OES], Fourier transform‐infrared [FT‐IR] spectroscopy, electrospray ionization mass spectrometry [ESI‐MS], thermogravimetric analysis [TGA], X‐ray photoelectron spectroscopy [XPS], X‐ray diffraction, and UV–Vis spectrophotometry). The resulted PGM‐loaded silica was successfully tested as a new heterogeneous catalyst for hydrosilylation and oxidation reactions. Information about the nature of the PGMs species extracted and loaded completes the existing literature data. The scrap cordierite may be valorized for retention of pollutants from water and also catalyzes the hydrosilylation reaction based on the remaining PGMs. Flexible composite materials can be obtained by incorporating scrap cordierite as filler and crosslinking catalyst into a silicone matrix, significantly enhancing the dielectric permittivity. Thus, complete re‐valorization of the main components of the catalytic converter as high‐added‐value materials was achieved at laboratory level, with very low energy demanding procedures. Abstract : Platinum group metals (PGMs) recovered from a spent catalytic converter were loaded into specially designed mesoporous silica by complexation with mercapto groups. The resulted material is a heterogeneous hydrosilylation and oxidation catalyst. The scrap cordierite after PGMs extraction finds use as crosslinking catalyst and filler for high permittivity silicone composites and in removal of organic pollutants from water.